Integrasi Etika dan Hukum dalam Bisnis: Strategi Keberlanjutan Perusahaan di Indonesia: Integration of Ethics and Law in Business: Corporate Sustainability Strategy in Indonesia - Annisa Khairin Pebrianti Nur; Nailah Nur Afiifah; Lisda Yanti AR; Budiarsih Budiarsih (Jurnal Hukum Bisnis, 2026)
This study analyses the integration of business ethics and legal compliance as a fundamental strategy for achieving corporate sustainability in Indonesia. The main issue studied focuses on the ongoing gap between formal legal compliance and the application of ethical responsibilities in daily business practices. Many companies comply with various statutory provisions but have not fully internalized ethical values as part of their organizational culture and decision-making processes. This study uses a normative-juridical approach by examining various relevant laws and regulations, corporate law concepts, and the latest scientific literature discussing business ethics, corporate governance, and business sustainability. The results show that legal compliance is an important foundation for conducting business activities. However, it is insufficient to ensure long-term corporate sustainability without the support of strong ethical values. Companies that integrate ethical principles into their business strategies and operations tend to have higher stakeholder trust, a better reputation, and lower legal, social, and reputational risks. Furthermore, implementing good corporate governance, corporate social responsibility, transparency, accountability, and the ability to adapt to technological developments and digital transformation are crucial factors in supporting business sustainability. Therefore, the synergy between business ethics and legal compliance is a strategic element that must be consistently implemented to create sustainable and competitive company growth.